Implementasi Supervisi Pendidikan di Era Digital - Qatrunnada Jinan Akmaliah; Selvi Dewi Rahayu; Haenul Jarya; Iswanto (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Educational supervision plays a role in improving the quality of learning, especially in the current digital era. Educational supervision is an important activity designed to improve the effectiveness and efficiency of teachers, one of which is teachers in schools. The implementation of educational supervision that is adaptive to technological developments can significantly improve the quality of learning. The implications of this study are the need to improve the competence of supervisors and teachers in utilizing digital technology, as well as the development of policies that support the implementation of effective supervision in the digital era. The research method used in this study is the library research method, which involves analyzing literature related to educational supervision and digital technology.